MALIGNANCY RATES OF ATYPIA OF UNDETERMINED SIGNIFICANCE/FOLLICULAR LESION OF UNDETERMINED SIGNIFICANCE (AUS/FLUS) CASES: A TERTIARY CENTER STUDY - Erdogan-Durmus, S.; Balta, H.; Demirtas, R.; Kurt, A. (Editura Acad Romane, 2021)
Aim. To evaluate the malignancy rates of Atypia of undetermined significance/follicular lesion of undetermined significance (AUS/FLUS) cases in the light of clinical and sonographic features. Material and Methods. The percentage of AUS/ FLUS cases, second fine needle aspiration cytology (FNAC) results, cyto-histopathological correlations and risk of malignancy were analyzed. Results. 113 out of 1461 thyroid FNAC samples (7.7%) were diagnosed as AUS/FLUS and included in the study. Seventy three out of 113 cases (64.6 %) underwent repeat biopsies or surgery. From 45 cases repeat biopsies were taken and 28 had thyroidectomy or lobectomy. There was a significant relation between nodule size and underwent surgery or repeat FNAC (p=0.036). Malignancy rate was 24.6% for cases which had any managements. The malignancy rates were higher in AUS/FLUS cases with cytological atypia (28.8%). After surgery the most common malignancy was papillary thyroid carcinoma, followed by follicular carcinoma. Conclusion. The risk of malignancy of AUS/FLUS cases is quite high because of the heterogeneity of the group. The sub-classification of this category according to cytological or/and architecture atypia may be more useful in predicting malignancy risk. Further larger studies with ancillary techniques including molecular analysis may be more useful in determining the malignancy risk and appropriate management of this heterogeneous category.
Keywords: thyroid nodules; malignancy; AUS/FLUS; Bethesda system